2013
DOI: 10.1590/s1677-5538.ibju.2013.02.11
|View full text |Cite
|
Sign up to set email alerts
|

The histology of prostate tissue following prostatic artery embolization for the treatment of benign prostatic hyperplasia

Abstract: Objective: Prostatic artery embolization (PAE) for the treatment of patients with symptomatic benign prostatic hyperplasia (BPH) is believed to be a safe procedure with a low risk of adverse side effects. Artery embolization is a viable treatment option in patients who are refractory to the classic noninvasive treatments. Knowledge of the histological characteristics of prostate tissue following the procedure is still limited. In this study, we describe the microscopic aspects of the prostate following PAE for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…This may be from the TURP achieving a radical resection of an enlarged volume. It may take longer after PAE to achieve the histopathologic changes associated with destruction of the prostate vasculature [17]. However, the PAE could not make a big change for non-radical removal of the prostate volume.…”
Section: Discussionmentioning
confidence: 99%
“…This may be from the TURP achieving a radical resection of an enlarged volume. It may take longer after PAE to achieve the histopathologic changes associated with destruction of the prostate vasculature [17]. However, the PAE could not make a big change for non-radical removal of the prostate volume.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IPSS and QoL, clinical success of PAE is also quantified in terms of Qmax, PV, PVR and IIEF. As the aim of PAE is to cause ischemic necrosis and shrinkage of the prostate gland (54), it is reasonable to assume that clinical improvement goes together with PV reduction and long-term PSA value decrease, in proportion with the extension of infarction area.…”
Section: Resultsmentioning
confidence: 99%
“…[1] It has been suggested that PAE results in a great reduction of prostate size, and that gland necrosis is the cause for reduction in prostate volume. [78] In one study, a patient had 47% volume reduction at 6 months following bilateral PAE, while another showed 28% reduction after unilateral PAE. [7] However, PAE has also been shown to successfully treat LUTS without reduction in prostate volume.…”
Section: Discussionmentioning
confidence: 99%